A DESCRIPTIVE EPIDEMIOLOGICAL STUDY ON MIGRAINE - MAMINDLA, POOJITHA; MOGILICHERLA, SHARANYA; ENUMULA, DEEPTHI; PRASAD, OM PRAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective was to carry out the observational study in migraine patients. Methods: A prospective observational study was conducted for 6 months in 415 migraine patients with the prior approval from the Institutional Ethical committee. A predesigned pro forma was used to collect data such as socio-demographics of the patients, different types of migraine, triggering factors, and prescription pattern. Results: Among 415 patients, the female patients (n=356, 86%) outnumbered male patients (n=95, 14%). The mean age of the study population was found to be 59±54 years. In our study, we found that migraine without aura (79%) was most common, followed by probable migraine without aura (13.3%), chronic migraines (5%), and migraine with aura (0.3%). Grading is done according to International Headache Society into 0, mild, moderate, and severe. Conclusion: Compared to migraine with aura, migraine without aura is mostly seen in females than males due to fluctuating hormone levels, rural area is most effected due to exposure to triggers. Management includes pharmacological and non-pharmacological. Pharmacological therapy included nonsteroidal anti-inflammatory drugs agents, Triptans, and prophylactic therapy, and adjunctive therapy also prescribed.